Stress mitigation of conventional water resources in water-scarce areas through the use of renewable energy powered desalination plants: An application to the Canary Islands. (February 2020) - Rosales-Asensio, Enrique; García-Moya, Francisco José; González-Martínez, Alberto; Borge-Diez, David; de Simón-Martín, Miguel
Abstract: Climate change conditions in the last decades have derived in a significant reduction of rivers' levels, irregularity of rainfall and, thus, difficulties in accessing to drinkable water. This situation is especially dramatical in islanded environments, such as the Canary Islands in Spain, where these restrictions to water resources have conducted to an overexploitation of aquifers and wells, with the deterioration of the environment that this fact entails. For this reason, desalination plants have become essential, and efforts must be done to reduce their impact and costs, as the involved processes for water desalination are high energy intensive. In this research paper, an optimized size hybrid wind and solar photovoltaic power plant is proposed to feed a desalination plant under the approach of not only feed the desalination process, but also provide the power grid with clean energy, taken advantage of the surplus electricity production. This way, not only the water resources stress is mitigated (through the desalting water production), but also the grid benefits from the integration of a distributed renewable energy source (DRES). Moreover, the business model is improved as the cost of drinkable water production is reduced and the power plant owner receives extra incomes from the water sales. Optimization results for a case study in Gran Canaria island shows that, considering the power dispatch in the island, the remuneration limits for power delivery and the remuneration for provided water, the optimal DRES associated with a desalination plant providing 5600 m 3 /day of desalted water and a maximum annual electricity injection to the power grid of 5.88 GWh/year, an hybrid solar PV and wind generation installation with electrochemical storage is a feasible solution that makes the Levelized Cost of Electricity ( LCOE ) achieve a singular reduced value despite considering the additional costs of the desalination plant, although financial help must be provided to reduce the Payback Time.